Effect of supercritical fluid density on nanoencapsulated drug particle size using the supercritical antisolvent method - Kalani M (Dove Medical Press, 2012)
Mahshid Kalani, Robiah YunusChemical and Environmental Engineering, Faculty of Engineering, University Putra Malaysia, Selangor Darul Ehsan, MalaysiaAbstract: The reported work demonstrates and discusses the effect of supercritical fluid density (pressure and temperature of supercritical fluid carbon dioxide) on particle size and distribution using the supercritical antisolvent (SAS) method in the purpose of drug encapsulation. In this study, paracetamol was encapsulated inside L-polylactic acid, a semicrystalline polymer, with different process parameters, including pressure and temperature, using the SAS process. The morphology and particle size of the prepared nanoparticles were determined by scanning electron microscopy and transmission electron microscopy. The results revealed that increasing temperature enhanced mean particle size due to the plasticizing effect. Furthermore, increasing pressure enhanced molecular interaction and solubility; thus, particle size was reduced. Transmission electron microscopy images defined the internal structure of nanoparticles. Thermal characteristics of nanoparticles were also investigated via differential scanning calorimetry. Furthermore, X-ray diffraction pattern revealed the changes in crystallinity structure during the SAS process. In vitro drug release analysis determined the sustained release of paracetamol in over 4 weeks.Keywords: supercritical antisolvent, encapsulation, supercritical fluid density, particle size